Business Communication ( Process & Product) - Guffey, Mary Ellen (South Western, 2015)
Business Communication: Process and Product provides you with extensive resources for eff ective and effi cient communication. The Seventh Edition’s preeminent technology coverage and groundbreaking technology resources are unrivaled. Authoritative and comprehensive, text content is thoroughly updated to refl ect the latest trends and advances in our increasingly digital world...